Fungsi Perjanjian Arbitrase - suphia suphia (Fakultas Hukum Universitas Islam Jember, 2015)
Disputes or disagreements can happen anytime and anywhere without being limited space and time as long as we live in a society. The most important thing in dispute or disagreement is how to resolve the dispute wisely. Many ways that can be taken to resolve the dispute or disagreement in the field of civil or trade. One form of alternative dispute resolution is a resolution through arbitration institution. Dispute resolution through arbitration agreement or clause requires that states that the parties agree to resolve a dispute that has existed or will exist between them will be resolved through arbitration. Arbitration agreement as a form of agreement, subject to the general provisions of the treaty as contained in the Code of Civil Law. Issues to be discussed in this paper is whether the function of the arbitration agreement or arbitration clause in a settlement of the dispute through arbitration.